A cross-sectional study on knowledge, attitude and practice of antenatal care among antenatal women attending a tertiary care hospital and its association with sociodemographic factors - Kilari, Sai Raja Nandini; Thirugnana, Sandhya Kandaswamy; Ganitha, G.; Kalaiselvi, Jikki (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Antenatal care (ANC) is essential for maternal and perinatal health through early detection of complications, nutritional support, immunisation, and health education. This study evaluated the knowledge, attitude, and practice (KAP) regarding ANC among antenatal women attending a tertiary care hospital and examined their association with sociodemographic factors. Methods: A cross-sectional study was conducted among 420 antenatal women at ACS Medical College and Hospital, Chennai, over six months. Data on socio demographics, obstetric history, and ANC-related KAP were collected using a structured questionnaire. Scores were categorised, and associations with participant characteristics were analysed using descriptive statistics and chi-square tests. Results: Of the 420 women, 244 (58.1%) demonstrated good knowledge, 126 (30.0%) average knowledge, and 50 (11.9%) poor knowledge. Attitudes were positive in 378 (90.0%), neutral in 17 (4.0%), and negative in 25 (6.0%), while practices were good in 294 (70.0%), fair in 84 (20.0%), and poor in 42 (10.0%). Participants aged 26–30 years had the highest knowledge (131, 53.7%), positive attitude (176, 46.6%), and good practices (143, 48.6%). Graduates (61.5%, 55.6%, 65.6%) and multigravidae (61.5%, 57.7%, 62.9%) consistently performed better than less educated or primigravida women. Employed women reported higher levels of knowledge (84.4%), attitude (62.2%), and practices (59.9%) compared to housewives. Women married at <25 years, with first pregnancy at 18–25 years, and those in the first trimester also showed higher KAP. Socioeconomic differences were minimal, though women from the lower middle class reported slightly better knowledge and practices. Conclusions: Most antenatal women demonstrated good knowledge, positive attitudes, and appropriate practices. KAP outcomes were significantly influenced by age, education, parity, occupation, and early pregnancy, highlighting the need for targeted education for younger, less educated, and primigravida women.